PENINGKATAN KOMPETENSI BERWACANA LISAN DENGAN METODE INVESTIGASI KELOMPOK - Mayong Maman (Faculty of Languages and Arts, Universitas Negeri Yogyakarta, 2012)
This study aims to describe the improvement in the process and outcomes of the spoken discourse learning through the group investigation method. The subjects were Year XI students of the Natural Science Program of SMAN 1 Sungguminasa South Sulawesi. This was a classroom action research study using a model by Elliot. The data were collected through observations and a performance test. The research findings were as follows. First, the group investigation method was capable of improving the students’ seriousness, enthusiasm, motivation, cognition, and skills in the implementation of the spoken discourse competence learning. Second, the method was capable of improving the students’ learning outcomes in each cycle. At the end of the cycle, the students’ activities in the learning process increased significantly.